"A child with sickle cell disease can't live with just anyone." A mixed methods study of socio‐behavioral influences and severity of sickle cell disease in northern Nigeria. Issue 1 (23rd December 2020) - Iliyasu, Zubairu; Borodo, Awwal M.; Jibir, Binta W.; Nass, Nafisa S.; Aliyu, Muktar H.
Abstract: Background: The modulatory effects of psychosocial and biophysical environments on sickle cell disease (SCD) severity during childhood has not been well characterized in high burden settings, such as Nigeria. Objectives: We identified socio‐demographic correlates and explored caregivers' perceptions on socio‐behavioral and environmental influences on hospitalization for pain and blood transfusion of children with SCD in Kano, Nigeria. Methods: Using mixed methods, structured questionnaires were administered to a clinic‐based sample of caregivers of children with SCD (n = 372), complemented with eight focus group discussions. Binary logistic regression models and the framework approach were used to analyze the data. Results: The majority (73.1%, n = 272) of the children had at least one vaso‐occlusive crisis (VOC), and 41.1% (n = 153) required hospitalization in the preceding year. A total of 170 children (45.7%) received blood transfusion. Hospitalization was predicted by the child's age (Adjusted Odds Ratio, AOR = 1.89; 95% Confidence Interval, CI: 1.18‐4.07, ≥10 vs <5 years), relationship with caregiver (AOR = 5.41; 95%CI: 1.17‐25.05, mother vs "others"), father's number of children (AOR = 2.21; 95%CI: 1.19‐5.31, ≥10 vs ≤4), and siblings with SCD (AOR = 2.36; 95%CI: 1.16‐8.80, 2 vs 0). Caregivers perceived maternal care, stable home environment, medication adherence, anti‐mosquito measures, and adequate nutrition as protective factors, whereas poverty, extreme emotions, physical exertion, and extreme temperatures were identified as detrimental to the health of the child. Conclusions: Hospitalizations for VOC and transfusion rates among children with SCD were high. Understanding the modulatory effects of socio‐behavioral factors on SCD severity could inform preventive measures and enhance the quality of life of affected children.